A review of the scholarly works on ChatGPT use in education: Bibliometric analysis - Wong Sing Yun; Sarimah Surianshah (ResearchGate, 2024)
The emergence of innovative artificial intelligence (AI) technologies, such as ChatGPT, which was just released in November 2022, has the potential to significantly transform the current state of education. Put another way, learning is changing as a result of chatbots' personalized assistance, group discussions and collaborations, evaluations of students' work, encouragement of self-directed learning, and raised student enthusiasm and engagement. A significant number of scholarly works has been done to examine the use of ChatGPT in education. This study aims to make a valuable contribution by conducting a bibliometric analysis of previous research, namely studies conducted throughout the study period, which mostly examined the implementation of ChatGPT in educational settings. The crucial data gathered from this analysis will help to identify the linkage and themes within the published literature. Lastly, this study will attempt to highlight the literature gap which future studies can be conducted in this very area of interest.